OP0237 A comparison of pk and pd outcomes of tocilizumab in giant cell arteritis after sc and iv dosing. (12th June 2018) - Mallalieu, N.L.; Stone, J.H.; Villiger, P.; Klearman, M.; Brockwell, L.; Dimonaco, S.; Charion, J.E.
Abstract : Background: Tocilizumab (TCZ), a humanised anti–interleukin-6 (IL-6) receptor monoclonal antibody, was recently approved for the treatment of patients with giant cell arteritis (GCA). Evidence was based on results of a double-blind randomised controlled trial (RCT) in GCA patients given 162 mg TCZ either weekly (QW) or every other week (Q2W) via subcutaneous (SC) route (GiACTA trial 1 ). A second RCT conducted using 8 mg/kg TCZ given intravenously (IV) every 4 weeks (Q4W) also showed positive outcomes in GCA patients. 2 The double-blind dosing portion of each study lasted approximately 1 year. All three regimens (SC 162 mg QW, SC 162 mg Q2W, IV 8 mg/kg Q4W) resulted in positive outcomes for sustained remission of GCA. However, a higher benefit was noted in some key secondary efficacy outcomes with the QW vs the Q2W SC regimen. 1 Objectives: To characterise the pharmacokinetics (PK) of TCZ in the GCA population and to assess the impact of the exposure differential from the three regimens on pharmacodynamic (PD) markers. Methods: TCZ levels and PD biomarkers (soluble IL-6 receptor [sIL-6R], IL-6, erythrocyte sedimentation rate [ESR], and C-reactive protein [CRP]) were measured using validated assays at regular intervals throughout the dosing period from all patients in each trial. A comparison of PK and PD outcomes was conducted to understand the dose exposure–response relationships. Results: At week 52, mean trough steady state exposure (Ctrough ), a primary PK driver of TCZ efficacy, was highest from SC 162 mg QW, followed by IV 8 mg/kg Q4W, and finally SC Q2W (figure 1). Of the PD end points, at week 52, sIL-6R levels were similar for the SC QW and IV regimens but lower for the SC Q2W regimen (figure 1), possibly demonstrating a higher level of target engagement from the SC QW and IV regimens compared with the Q2W regimen. IL-6 levels increased vs baseline after TCZ administration for all three regimens, reflecting displacement of bound, endogenous IL-6 from its receptor, consistent with the mechanism of action of TCZ. ESR levels decreased to a similar extent in response to TCZ administration with all three regimens. Change from baseline in CRP was comparable between the two SC regimens (~79%–93% reduction from baseline from the QW and Q2W regimens, respectively). Quantitative changes in CRP values are not available for the IV study. Conclusions: Comparison of Ctrough after 52 weeks of dosing with TCZ from the 8 mg/kg IV regimen with that obtained from two SC regimens showed that exposures from the IV regimen were within the range of exposures of the QW and Q2W regimens. Comparison of PD outcomes showed that all three regimens had comparable results, with the possible exception of lower levels of sIL-6R (a mechanistic marker reflecting serum concentration and target engagement) from the SC Q2W regimen. Comparability of PD results is consistent with the similar efficacy outcomes seen in the SC and IV trials. References: [1] Stone JH, et al. N Engl J Med2017;377:317–328. [2] Villiger PM, et al. Lancet2016;387:1921–1927. Acknowledgements: This study was sponsored by F. Hoffmann-La Roche Ltd. Disclosure of Interest: N. L. Mallalieu Shareholder of: Roche, Employee of: Roche, J. H. Stone Grant/research support from: Roche, Genentech, Xencor, Consultant for: Roche, Genentech, Xencor, P. Villiger: None declared, M. Klearman Employee of: Genentech, L. Brockwell Employee of: Roche, S. Dimonaco Employee of: Roche, J. E. Charion Employee of: Roche